Identifying urban hotspots of potential bird and pedestrian encounters through corridor overlap - Verweij, Emma E.; Pena, João Carlos [UNESP]; Assis, Julia C. (Springer Nature, 2025)
One way people living in urban areas interact with wildlife is through encounters with birds. Research shows that visual and acoustic interactions with birds enhance the quality of life for city residents. However, global habitat loss and fragmentation have led to declines in most urban bird populations. As urbanization accelerates worldwide, it is essential to find ways for bird populations to thrive in cities while meeting citizens’ cultural ecosystem service needs. This study utilized least-cost path models to identify (i) potential ecological corridors between green spaces for six Dutch urban bird species experiencing population decline and (ii) locations that present a high likelihood of encounters between these birds and pedestrians in urbanized areas. Using expert knowledge, we simulated multiple least-cost corridors among nine green spaces in the Municipality of Utrecht. Additionally, we determined the best potential paths for pedestrians between the same nine green spaces based on citizen science data. Our results revealed that the multi-species nature of bird corridors varies, and there is limited overlap between these corridors and the simulated pedestrian paths. Nonetheless, most bird corridors are situated within 20 m of pedestrian paths, indicating hotspot areas with high potential for bird-pedestrian encounters, particularly near the Utrecht city center. We contend that locations where pedestrian paths intersect or are close to the simulated bird corridors are ideal for interventions aimed at increasing landscape permeability for the six bird species, ultimately enhancing the chances of encounters between birds and pedestrians. Finally, we proposed conservation measures based on our findings that benefit both the studied bird guilds’ population growth and the daily lives of citizens.
Keywords: Human-nature interaction; Landscape connectivity; Multiple least-cost corridors; Urban bird species; Urban green